(untitled) (Research, Society and Development, 2022)
Rehabilitation in atrophic maxilla brings challenges due to the continuous and progressive alveolar resorption and alveolar pneumatization of the maxillary sinus, which makes rehabilitation with conventional size implants unfeasible. One of the alternatives for these cases is the use of narrow implants. Thus, the aim of the present study was to verify the viability of narrow implants in the total rehabilitation of the atrophic maxilla. The photoelastic analysis method was used, creating six groups: GC1 (4.1 mm x 10.0 mm), GC2 (4.1 mm x 12.0 mm), NC1 (3.3 mm x 10.0 mm), NC2 (3.3 mm x 12.0 mm) , SC1 (2.9 mm x 10.0 mm) and SC2 (2.9 mm x 12.0 mm) that were evaluated in the circular polariscope model PTH-A-01 (LPM/FME/UFU) with centric loading, left/right laterality and 5 N protrusive The models were tested, photographed and analyzed according to isometric fringe orders. The analysis of color patterns and location aided in the quantitative-qualitative interpretation and tensions of the subgroups tested arising from the forces on osseointegrated implants arranged in an arch, “all-on-four” rehabilitation type in the maxilla. The evaluated groups showed a positive interaction in relation to the increase in the diameter of the implants, with a decrease in the stress concentration for the region of the central implants. No difference was observed between the groups in the protrusive loading and, in relation to the distal loadings, the stresses in all groups ranged from low to high. Thus, in general, no significant differences were found in relation to narrow implants when compared to regular diameter implants.